Range extension of Marchantia formosana (Marchantiaceae, Marchantiophyta), with an updated key to Marchantiaceae taxa in East Asia - Zheng, Tian-Xiong; Long, David G.; Shimamura, Masaki (Phytotaxa, 2023)
Marchantia formosana is newly reported from Yunnan, China. An updated key to the East Asian taxa of the family Marchantiaceae is also provided.